Bottom-up and Climatic Forcing on the Worldwide Population of Leatherback Turtles - Saba, V.S; Spotila, J.R; Chavez, F.P; Musick, J.A (Ecology (Durham), 2008)
Nesting populations of leatherback turtles (Dermochelys coriacea) in the Atlantic and western Indian Oceans are increasing or stable while those in the Pacific are declining. It has been suggested that leatherbacks in the eastern Pacific may be resource limited due to environmental variability derived from the El Niño Southern Oscillation (ENSO), but this has yet to be tested. Here we explored bottom-up forcing and the responding reproductive output of nesting leatherbacks worldwide. We achieved this through an extensive review of leatherback nesting and migration data and by analyzing the spatial, temporal, and quantitative nature of resources as indicated by net primary production at post-nesting female migration and foraging areas. Leatherbacks in the eastern Pacific were the smallest in body size and had the lowest reproductive output due to less productive and inconsistent resources within their migration and foraging areas. This derived from natural interannual and multidecadal climate variability together with an influence of anthropogenic climate warming that is possibly affecting these natural cycles. The reproductive output of leatherbacks in the Atlantic and western Indian Oceans was nearly twice that of turtles in the eastern Pacific. The inconsistent nature of the Pacific Ocean may also render western Pacific leatherbacks susceptible to a more variable reproductive output; however, it appears that egg harvesting on nesting beaches is their major threat. We suggest that the eastern Pacific leatherback population is more sensitive to anthropogenic mortality due to recruitment rates that are lower and more variable, thus accounting for much of the population differences compared to Atlantic and western Indian turtles.